Financial Performance and Dividend Policy - Kimunduu, Geoffrey Mbuva; Mwangi, Mirie; Kaijage, Erasmus; Ochieng, Duncan Elly (European Scientific Journal, ESJ, 2017)
Past studies on the relationship between dividend policy and firm performance continue being an unresolved predicament with few studies interrogating the causality relationship between financial performance and dividend policy. The purpose of this study was to establish the nature of relationship between financial performance and dividend policy of firms listed at the Nairobi securities exchange. The study applied positivism research philosophy and descriptive causal research design. The study was anchored on hypothetical view that the relationship between financial performance and dividend policy of firms listed at the Nairobi securities exchange is not significant which was tested against a sample size of 31 firms listed at the Nairobi securities exchange selected using purposive sampling technique. The research findings were as follows: There was a statistically significant direct association between return on equity and dividend policy. This implies that as firm profitability improve; a corresponding proportionate change in dividend payout ratio is initiated by management. In addition, it was established that there was a statistically significant positive linkage between operating cash flows and dividend policy which denotes that as cash flow levels from operating activities change, dividend payout ratio will change in the same direction leading to increased distribution of cash dividend to investors. Also, a statistically significant direct connection between price earnings and dividend policy was established. This relationship shows that increase in share market value positively prompts increased dividend payout ratio whereby the management follow a more acceptable dividend policy by the shareholders. However, market to book value depicted a weak insignificant inverse relationship with dividend policy and was dropped. In general it was concluded that the link between financial performance and dividend policy of firms listed at the Nairobi securities exchange was significant. The study outcome augment existing knowledge on financial performance and dividend policy for it is evident that firms with ability to generate income directly influence dividend payout ratio and therefore, top management should focus on financial performance strategies and not dividend policy which is irrelevant. Regulatory bodies such as Capital Market Authority and Centre for Corporate Governance use these research findings to improve their financial viability assessment approach of firms listed at the Nairobi securities exchange.